Fabrication of bioinspired super-hydrophilic nano-fibrous membrane for oil-water separation and directional water transportation - Li, Zhengtao (Nanyang Technological University, 2020)
Energy efficient water purification and transportation is the key to solve energy and water crisis throughout the world. Inspired by the natural special wetting surfaces, many super-hydrophobic materials were fabricated and studied for efficient oil-water separation and directional water movement. However, due to some limitations of hydrophobic materials, super-hydrophilic materials are more regarded as the candidate to overcome those shortcomings to achieve efficient oil-water separation and bulk water transportation.